Effectiveness of Chromolaena odorata L. cream in reducing melanocyte cell count and TNF- levels in male Wistar rats exposed to UVB radiation - Sari, Maya; Yusuf, Hanifah (School of Medicine, Universitas Syiah Kuala, 2025)
Chromolaena odorata L. is a plant traditionally used in herbal medicine. The leaves of C. odorata contain bioactive compounds with high antioxidant activity, making them potential therapeutic agents for hyperpigmentation and inflammation. Ultraviolet (UV) radiation is an extrinsic factor and a major cause of skin aging, known as photoaging. Photoaging is a process due to chronic UV exposure that induces the formation of reactive oxygen species (ROS). Excess ROS, surpassing body's antioxidant capacity, leads to skin barrier damage, DNA damage, and hyperpigmentation. Photoprotection is essential to mitigate these effects. The aim of this study was to evaluate the antioxidant activity of C. odorata leaf ethanol extract cream and its effect on melanocyte cell and tumor necrosis factor alpha (TNF-) levels in male Wistar rats (Rattus norvegicus). A true experimental post-test with control group design was used, involving 42 male Wistar rats divided into seven groups: Group Ino UVB exposure, cream base only; group IIUVB exposure only; group IIIUVB exposure with cream base; group IVUVB exposure with 5% C. odorata ethanol extract cream; group VUVB exposure with 10% C. odorata ethanol extract cream; group VIUVB exposure with 2% hydroquinone cream; and group VIIUVB exposure with 5% vitamin C cream. C. odorata extract was formulated into a cream and tested for antioxidant activity using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay. The cream was topically applied to rats dorsal skin irradiated with UVB for three weeks following a scheduled exposure protocol. At weeks 3 and 6, three rats per group were euthanized using cervical dislocation, and 55 cm dorsal skin samples were collected for histological analysis of melanocyte count and TNF- levels via enzyme-linked immunosorbent assays (ELISA). The results showed that C. odorata ethanol extract cream contained strong antioxidants with an IC50 of 57.7 mg/L. Statistical analysis revealed significant differences in melanocyte count and TNF- levels among groups at weeks 3 and 6 (p0.05). The 10% C. odorata extract cream had the lowest melanocyte counts, while the 5% C. odorata extract cream exhibited the lowest TNF- levels, indicating the extracts photoprotective and anti-inflammatory effects.